Exploratory Visuals and Text in Qualitative Research Interviews: How Do We Respond?. (20th June 2022) - Page, Jude; Broady, Timothy; Kumar, Sujith; de Leeuw, Evelyne
Visual stimuli are increasingly used in formal communications and as a qualitative research method, reported to generate a 'different' and 'richer' response than text or language alone. However, the parameters by which this occurs are underexplored. In our research we use images and text as interview stimuli in a project exploring personal wellbeing to compare differences in communication process and outcomes. A visual tool expressing concepts of human needs and aspirations and comparable text was presented on cards. Forty-five people participated in a sorting process and interview. Participants were presented with the text cards or images first in blocked order and asked to select cards relating to their wellbeing. The process was repeated with the alternate mode. A subsection of six participants were presented with text-image combination cards. Thematic analysis was used to find common themes in participant responses and their experiences of the two modalities. Image and text cards both facilitated communication and rapport but elicited different types of responses. Images more commonly provoked emotive responses, tacit knowledge and greater personal involvement leading to cognitive elaboration and richer narrative. We found that participants more easily selected visual themes and considered images more engaging and open to interpretation than text, which were considered fixed in meaning. When visuals were presented with text, the text dominated the meaning. This paper presents a novel form of researcher generated visual elicitation stimuli, to be called 'exploratory visuals'; depicting abstract concepts and narrative scenes to aid communication and understanding of complex information. It proposes an analytical framework combining social semiotic, contextual and cognitive perspectives to understand perceptual differences between words and images and the range of responses elicited.